Comparison of Different Control Techniques for Interleaved DC-DC Converter - M. Kavitha; V. Sivachidambaranathan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Interleaved DC-DC converter with coupled inductor is used in standalone Photovoltaic, battery charger/discharger application. The main issue of the Interleaved DC-DC converter is that, it does not provide constant output voltage for a change in input voltage. Therefore, the converter efficiency is reduced. Hence to overcome this drawback, proper controller has to be used. In this paper, different control techniques such as PI, PID and Fuzzy logic controller are used. The simulation results of all three controllers were done using MATLAB/Simulink and compared. Fuzzy logic controller provides better regulated output voltage with less settling time of 0.04sec.